The Analysis of Office Management at Government Agency Offices to Provide Public Services in Warudoyong Sukabumi - Ajeng Rosmaula; Anggi Maulana; Ai Restaria; Muhamad Wildan Mailidan; Tia Nuraini; Alfin Fauzan (GoResearch - Research & Publishing House, 2023)
Abstract Office management in government agencies plays an important role as a management catalyst in achieving public services. Public service is an effort in providing services provided by an organization or agency in meeting customer needs in accordance with the principles and principles of public service. The purpose of this research is to analyze and understand office management and services in Warudoyong Sub-district, Sukabumi City. The research method used is descriptive research through a qualitative approach. The results of the research are that the Warudoyong Sub-district apparatus always works together in providing the best service to the community, besides that in the implementation of public services, service standards must be prepared by the organizer by taking into account the organizer's capabilities, community needs, and environmental conditions. Keywords: Community, Service, Office, Warudoyong.